Dynamics of CYP51: implications for function and inhibitor design - Yu, Xiaofeng; Cojocaru, Vlad; Mustafa, Ghulam; Salo‐Ahen, Outi M. H.; Lepesheva, Galina I.; Wade, Rebecca C. (Journal of molecular recognition, 2015)
Sterol 14α-demethylase (cytochrome P450 family 51 (CYP51)) is an essential enzyme occurring in all biological kingdoms. In eukaryotes, it is located in the membrane of the endoplasmic reticulum. Selective inhibitors of trypanosomal CYP51s that do not affect the human CYP51 have been discovered in vitro and found to cure acute and chronic mouse Chagas disease without severe side effects in vivo. Crystal structures indicate that CYP51 may be more rigid than most CYPs, and it has been proposed that this property may facilitate antiparasitic drug design. Therefore, to investigate the dynamics of trypanosomal CYP51, we built a model of membrane-bound Trypanosoma brucei CYP51 and then performed molecular dynamics simulations of T. brucei CYP51 in membrane-bound and soluble forms. We compared the dynamics of T. brucei CYP51 with those of human CYP51, CYP2C9, and CYP2E1. In the simulations, the CYP51s display low mobility in the buried active site although overall mobility is similar in all the CYPs studied. The simulations suggest that in CYP51, pathway 2f serves as the major ligand access tunnel, and both pathways 2f (leading to membrane) and S (leading to solvent) can serve as ligand egress tunnels. Compared with the other CYPs, the residues at the entrance of the ligand access tunnels in CYP51 have higher mobility that may be necessary to facilitate the passage of its large sterol ligands. The water (W) tunnel is accessible to solvent during most of the simulations of CYP51, but its width is affected by the conformations of the heme's two propionate groups. These differ from those observed in the other CYPs studied because of differences in their hydrogen-bonding network. Our simulations give insights into the dynamics of CYP51 that complement the available experimental data and have implications for drug design against CYP51 enzymes. Copyright © 2015 John Wiley & Sons, Ltd.
Gesehen am 14.07.2020